Ecological Justice in River Water Pollution Control Policy in Jakarta Through DPSIR Analysis - Untoro Untoro; Otom Mustomi; Mardani Mardani; Fadhil Athif Ananda Putra (AMCA Journal of Community Development, 2026)
River water pollution in Jakarta is a national and international concern that requires serious attention. Therefore, environmental information, including ecological vulnerability maps, environmental status, and other relevant data, is crucial for effective environmental management. A regional environmental analysis and policy evaluation in 2024, using the DPSIR method, identified the environmental impact of river water conditions in real-time through water status measurements and aquatic ecological indicators. From the periodic analysis of Main Pollutant Parameters (MPP) during 2018-2024, eight parameters, such as fecal coliform, total coliform, free chlorine (Cl2), hydrogen sulfide (H2S), BOD, phenol, and ammonia (NH3), were classified as river MPPs. Specifically, fecal coliform, total coliform, and ammonia (NH3) have consistently been river MPPs in Jakarta during the 2018-2024 monitoring period, requiring primary attention due to their high and continuous pollution levels.